A new normal?: women's experiences of biographical disruption and liminality following treatment for early stage breast cancer - Trusson, Diane; Pilnick, Alison; Roy, Srila (Elsevier, 2016)
Increasing numbers of women are surviving breast cancer, but little is known about the long-term implications of having survived a life-threatening illness and living with embodied reminders of its potential to return. Twenty-four women aged between 42 and 80 (median 1/4 51)who had been treated for early stage breast cancer in the UK between 6 months and 29 years previously, were recruited through local media and interviewed. Analysis of their narratives revealed challenges in the post-treatment period that were conceptualised as biographical disruption and liminality. Although no longer ill, an ongoing fear of recurrence combined with embodied changes prevented a return to ‘normal’ i.e. a pre-cancer state in terms of health status, identity and relationships. We argue that following the biographical disruption of breast cancer, a ‘new normal’ entails a continual renegotiation of identities, daily lives and futures as time passes and lives evolve.